Brazil as a Security Actor in Africa: Reckoning and Challenges Ahead - Seabra, Pedro (GIGA Focus Latin America, 2016)
The story of Brazil’s engagement in Africa is not necessarily novel, but its security activities on the continent still are. Often presented as by-products of the new South–South relations, they have resulted in substantial inroads towards the increased security capacity of several key countries. However, economic constraints, an unpredictable political context back home, and previously existing structural fragilities have led to a new, bleaker outlook for Brazil’s position in Africa.